Shifts from English into Bahasa Indonesia of Zig Ziglar’s “See at the top” - RISNAWATY, RISNAWATY; SUTIKNO, SUTIKNO; ANDRIANY, LIESNA; SIREGAR, ROSWANI (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This article is aimed at identifying the shift in the Indonesian translation from “See You At the Top.” Translators would tend to translate his materials with one or more strategies. However, in the interpretation of English as a source text into Indonesian as the target text (TT), it was found that shift became the most commonly used. The shift in meaning and form might always become problems in the TT since it changes the original forms of words, phrases, clauses, and sentences in ST. Findings revealed that shift from words to phrases reached 35.4%, from phrases to words 10.32 %, and from phrases to sentences 54%.